Disrupting Patriarchy Through Critical Literacy: A Textual and Pedagogical Analysis of Faqihuddin Abdul Kodir’s Writings on Gender Justice in Contemporary Indonesia - Muhamad Fathi Ilmy; Ilman Nafi'a; Septi Gumiandari; Huriyah Huriyah; Nazwa Ilmy (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Patriarchal narratives in Indonesian educational and religious texts continue to reproduce gender inequality, making critical literacy an urgent pedagogical approach. This study aims to examine how the works of Faqihuddin Abdul Kodir contribute to promoting gender justice in language education through critical literacy practices. Employing a qualitative case study design, the research involved interviews, classroom observations, and document analysis with language teachers and education students in Cirebon who engaged with Faqihuddin’s writings and mubadalah framework. The findings reveal that teachers and students developed greater awareness of gender bias in texts and adopted reflective reading strategies to internalize ethical values such as justice and reciprocity. Teachers began to integrate inclusive language and encourage rewriting exercises from female perspectives, which positioned students as agents of social change. Furthermore, educators started to redefine their professional roles from mere linguistic instructors to facilitators of social justice. These results demonstrate the transformative potential of gender-just critical literacy pedagogy in both Islamic and multilingual educational contexts. This study concludes that integrating gender-conscious texts and reflective practices can enrich language classrooms, advance gender equality, and offer a progressive Islamic contribution to global critical literacy discourse.